Sense of Coherence in Young People with Congenital Heart Disease. Issue 4 (May 2015) - Apers, Silke; Luyckx, Koen; Goossens, Eva; Rassart, Jessica; Budts, Werner; Moons, Philip
ABSTRACT: Objective: Patient-reported outcomes (PROs) have been found to play a role in the development of clinical complications. Hence, it is crucial to understand why some patients do well in terms of PROs and others do not and to identify these groups of patients. Sense of coherence (SOC), capturing a person's outlook on life, is associated with PROs in adolescents with congenital heart disease (CHD). Therefore, we (1) examine how SOC develops in young people with CHD, (2) identify subgroups of SOC development, and (3) characterize subgroups in terms of demographic and clinical variables and PROs. Method: In this 4-wave longitudinal study, 429 adolescents with CHD (53.4% boys; median age = 16.3 years) completed assessments of SOC (SOC-13). PROs included quality of life (linear analog scale), loneliness (UCLA-8), depression (CES-D), and perceived health (PedsQL). Latent class growth analysis was used to identify clinically meaningful subgroups of SOC development. Results: Patients with CHD had a moderate SOC that slightly decreased over the first 18 months. Four subgroups of SOC development emerged: Consistently High (27%), Intermediate Stable (41%), Intermediate Decreasing (25%), and Chronically Low (7%). Subgroups differed in terms of sex and PROs, but not in terms of age, disease complexity, primary diagnosis, or surgical history. Conclusion: Patients with a strong and stable SOC over time showed a better adaptation than patients with a lower and/or decreasing SOC. Our results can guide the identification of patients at risk for adverse health outcomes and the development of interventions to enhance optimal living in patients with CHD.